2014
DOI: 10.1038/bjc.2014.237
|View full text |Cite
|
Sign up to set email alerts
|

A clue towards improving the European Society of Medical Oncology risk group classification in apparent early stage endometrial cancer? Impact of lymphovascular space invasion

Abstract: Background:Lymphovascular space invasion (LVSI) is one of the most important predictors of nodal involvement and recurrence in early stage endometrial cancer (EC). Despite its demonstrated prognostic value, LVSI has not been incorporated into the European Society of Medical Oncology (ESMO) classification. The aim of this prospective multicentre database study is to investigate whether it may improve the accuracy of the ESMO classification in predicting the recurrence risk.Methods:Data of 496 patients with appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 29 publications
3
55
0
3
Order By: Relevance
“…However, Briet et al13 suggested that lymphovascular space invasion itself may individually be used to assign stage I low-risk patients to adjuvant therapy in order to decrease the failure rate and thereby improve the survival. Additionally, the European Society for Medical Oncology-modified criteria35 has recently introduced lymphovascular space invasion as the cornerstone of risk stratification in endometrioid endometrial cancer. Regardless of myometrial invasion, the European Society for Medical Oncology-modified criteria recommends adjuvant treatment for all grade 1 or 2 endometrioid type tumors if lymphovascular space invasion is unequivocally positive.…”
Section: Discussionmentioning
confidence: 99%
“…However, Briet et al13 suggested that lymphovascular space invasion itself may individually be used to assign stage I low-risk patients to adjuvant therapy in order to decrease the failure rate and thereby improve the survival. Additionally, the European Society for Medical Oncology-modified criteria35 has recently introduced lymphovascular space invasion as the cornerstone of risk stratification in endometrioid endometrial cancer. Regardless of myometrial invasion, the European Society for Medical Oncology-modified criteria recommends adjuvant treatment for all grade 1 or 2 endometrioid type tumors if lymphovascular space invasion is unequivocally positive.…”
Section: Discussionmentioning
confidence: 99%
“…In this specific setting, many centers in the United States perform lymph node sampling, 5,6 rates that can be higher in the case of lymphovascular space involvement (LVSI) on the primary tumor. [7][8][9] It is now well established that conventional methods used for histologic classification and grading of EC are not sufficient to predict lymph node metastases. This is probably due to considerable heterogeneity within endometrioid histologic subtypes.…”
mentioning
confidence: 99%
“…Most uterine cancers have a favorable prognosis and are cured by surgery alone. Identifying patients at risk of recurrence, particularly those misclassified as low risk by current clinicopathologic standards [3][4][5][6][7][8][9] is of paramount importance. Physicians need better risk stratification tools to identify when and which adjuvant therapy will decrease recurrence.…”
Section: Nestin Commentarymentioning
confidence: 99%